A 3D porous Ni–Cu alloy film for high-performance hydrazine electrooxidation. Issue 3 (17th December 2015) - Sun, Ming; Lu, Zhiyi; Luo, Liang; Chang, Zheng; Sun, Xiaoming
Abstract : A porous Ni–Cu alloy film was fabricated by a one-step electrodeposition method and performed high activity and stability in HzOR. Abstract : Structural design and catalyst screening are two most important factors for achieving exceptional electrocatalytic performance. Herein we demonstrate that constructing a three-dimensional (3D) porous Ni–Cu alloy film is greatly beneficial for improving the hydrazine oxidation reaction (HzOR) performance. A facile electrodeposition process is employed to synthesize a Ni–Cu alloy film with a 3D hierarchical porous structure. As an integrated electrode for HzOR, the Ni–Cu alloy film exhibits superior catalytic activity and stability to the Ni or Cu counterparts. The synthesis parameters are also systematically tuned for optimizing the HzOR performance. The excellent HzOR performance of the Ni–Cu alloy film is attributed to its high intrinsic activity, large electrochemical specific surface area, and 3D porous architecture which offers a "superaerophobic" surface to effectively remove the gas product in a small volume. It is believed that the Ni–Cu alloy film electrode has potential application in direct hydrazine fuel cells as well as other catalytic fields.